STUDI KASUS MANFAAT PENERAPAN TERAPI MENGGAMBAR PADA KLIEN DENGAN HARGA DIRI RENDAH KRONIS (HDRK) DI RSJD dr. ARIF ZAINUDIN SURAKARTA - Valerio Basuni Carlo Caryanto; Wahyudi Mulyaningrat (Jurnal Ilmu Keperawatan Jiwa, 2024)
The World Health Organization or World Health Organization in 2022 stated that 1 in 8 people in the world experience mental disorders or 970 million people in the world, in Indonesia around 1 in 5 people experience mental disorders or around 20% of 250 million people, one of which is a lot of mental disorders. experienced is chronic low self-esteem. Chronic low self-esteem is negative feelings about oneself. Drawing therapy is a therapy using art media to express feelings and communicate. Drawing therapy has been widely used in medical environments, one of which is for the treatment of mental disorders. The aim of the research is to identify the benefits of applying drawing therapy to reduce chronic low self-esteem in clients at RSJD dr. Arif Zainudin Surakarta, case study research method using the application of evidence based paratice in providing nursing care to clients. The application of drawing therapy was carried out 3 times during 3 days of therapy with the results that there were benefits of applying drawing therapy to the patient's recovery. The conclusion of the research carried out is that drawing therapy activities provide benefits in reducing the signs and symptoms of chronic low self-esteem. Suggestions before conducting research are to build a relationship of mutual trust and explore positive aspects with the aim of making it easier to carry out the interventions taken and those that will be carried out on clients.